The South Andean woman in the town of God - Lapiedra, Aurora (1984)
"God has chosen those whom the world considers fools, to shame the wise; and he has chosen those whom the world considers weak, to shame the strong. God has chosen those who are of no importance in the world and are despised, that is, those who are nothing, to put an end to those who are something, so that no one can feel proud before God." (1 Cor. 1, 27-29). The poor in the Andean world are part of this sector chosen by God that Saint Paul speaks of. They have a significant prophetic and apocalyptic presence of the Christian God, which is what constitutes them in a theological place, that is, in a privileged place of revelation of God, praxis and Christian reflection.